Outcomes and risk factors of mechanical circulatory support by peripheral venoarterial extracorporeal membrane oxygenation in heart transplant candidates needing urgent heart transplantation - V. N. Poptsov; V. M. Zakharevich; E. A. Spirina; S. G. Uhrenkov; A. A. Dogonasheva; E. Z. Aliev (Вестник трансплантологии и искусственных органов)
Introduction Peripheral veno-arterial extracorporeal membrane oxygenation (VA ECMO) is one of the most frequently used methods of temporary mechanical circulatory support (MCS) at patients with life-threatening circulatory derangement.Aim: to evaluate the effectiveness and risk factors of peripheral VA ECMO in patients waiting of urgent heart transplantation (HT). Materials and methods. The study included 149 (129 (86.6%) men and 20 (13.4%) women, age 12 to 72 (43.0 ± 1.2) years) heart transplant candidates who in the period 01.01.2011–31.12.2016 were supported by peripheral VA ECMO. These patients were 21.1% of the total waiting list (n = 706) of our institute at the same period. Indication for MCS by VA ECMO was advanced heart failure corresponding to I or II level of INTERMACS classiﬁ cation.Results. 135 (90.6%) from 149 patients were successfully supported to HT. 14 (9.4%) deed following MCS. Before of VA ECMO these patients (n = 14) had more severe (p < 0.05) hemodynamic disorders, organ dysfunction, electrolyte and metabolic disorders compared to patients TC successfully supported to HT. Left atrium (n = 24)/left ventricle drainage (n = 8) was performed for volume decompression of left heart (n = 32 (21.5%)). In a single-factor analysis, statistically signiﬁ cant pre VA ECMO risk factors for the lethal outcome were: creatinine ≥ 140 mmol/l, urea ≥ 15 mmol/l, total bilirubin ≥ 80 μmol/l, ALT ≥ 300 U/l, AST ≥ 300 U/l, INR ≥ 3.0, procalcitonin ≥ 3.0 ng/ml, preexisting left ventricular thrombosis complicated thromboembolic stroke with brain death following VA ECMO (n = 3). Statistically signiﬁ cant factors for the lethal outcome following MCS were: transthoracic left ventricle drainage (n = 8) compared to transcutaneous transfemoral transseptal left atrium drainage (n = 24) for volume decompression of left heart; hemolysis ≥ 300 mg%. Conclusion. VA ECMO is high efﬁ ciency method of temporary MCS in 90.6% heart transplant candidates needed at urgent HT. VA ECMO must be begin before development of potential lethal multiorgan and septic complications. Preexisting left ventricular thrombosis increase risk of lethal thromboembolic brain injury following VA ECMO. Patients with transcutaneous transfemoral transseptal left atrium drainage for left heart volume decompression had better outcome following MCS by VA ECMO.